2015
DOI: 10.5388/aon.2015.15.2.89
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Human Papillomavirus Vaccination Adoption Stages Based on the Precaution Adoption Process Model

Abstract: 연구의 필요성여성의Purpose: This study aimed to identify the factors influencing human papillomavirus (HPV) vaccination adoption stages using the Precaution Adoption Process model. Methods: A total of 173 female university students from B metropolitan city participated. Demographics, factors contributing to action, knowledge, health beliefs, and self-efficacy related to the HPV vaccination were measured. The collected data were analyzed using descriptive statistics and multiple logistic regression analysis using SPSS f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…However, in the case of a persistent infection, it goes through cervical dysplasia and progresses to cervical cancer (Centers for Disease Control and Prevention, USA, 2019;WHO, 2019). The result of the analysis of the infection status of 60,775 women in South Korea from 2006 to 2011 showed that 49.9% of HPV-infected positive women aged 18 to 29 years old have shown a high incidence of infection among young people who begin their first sexual life (Korea Centers for Disease Control and Prevention, 2019; E. N. Lee et al, 2015). HPV has a low natural antibody production rate (WHO, 2019), and there is no way to cure the infection itself.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, in the case of a persistent infection, it goes through cervical dysplasia and progresses to cervical cancer (Centers for Disease Control and Prevention, USA, 2019;WHO, 2019). The result of the analysis of the infection status of 60,775 women in South Korea from 2006 to 2011 showed that 49.9% of HPV-infected positive women aged 18 to 29 years old have shown a high incidence of infection among young people who begin their first sexual life (Korea Centers for Disease Control and Prevention, 2019; E. N. Lee et al, 2015). HPV has a low natural antibody production rate (WHO, 2019), and there is no way to cure the infection itself.…”
Section: Literature Reviewmentioning
confidence: 99%